Significant Elements of Islamic Capital Market - Issoufou, Chaibou (International Journal of Engineering and Technology, 2018)
There is no doubting the importance of the Islamic capital market particularly its elements. These elements are crucial for boosting the economy of a country and providing funds for a project. The development of any country is based on its capital market elements which are trading in the market. This paper examines and explores the nature of Islamic capital elements such as Islamic Real Estate Investment Trust, Islamic Unit Trust as well as Sukuk. The paper elaborates the significance of Sukuk in the contemporary era and Shari‘ah issues on Sukuk. The study adopts a qualitative research methodology in which the researcher analyses principles of Islamic jurisprudence on the issues pertaining to elements of Islamic capital market. The study finds that not all companies are eligible to invest elements of Islamic capital market such as non-halal companies are not eligible to invest Islamic capital elements. Thus, for a company to be eligible to invest such elements, its activities must be halal or must attain certain benchmarks as determined by the Malaysian Shari‘ah Advisory Committee of the Securities Commission. The study also discovers that Sukuk is the most significant element in the market and many Sukuk structures need enhancement to conform with the principles and regulations of Islamic law.